Destination brand awareness and perceived value: the mediating influence of destination image - Aldio Ferdinando; Yasri Yasri (Marketing Management Studies, 2023)
The purpose of this study is to analyze the extent of the influence of destination brand awareness and destination image in increasing perceived value in Gandoriah Beach tourist attractions. The population in this study is all people who have visited the Gandoriah Beach Tourist Area, the number of which is not known with certainty. Meanwhile, the number of samples in this study was 110 respondents using the purposive sampling method. The analysis technique used is SEM analysis using smart PLS3. The results of the study are (1) There is a significant influence between destination brand awareness and perceived value. (2) There is a significant influence between destination brand awareness and destination image. (3) There is a significant and positive influence between destination image and perceived value. (4) Destination image is able to mediate the influence of destination brand awareness with perceived value.